The efficacy and adverse reaction of bleeding of clopidogrel plus aspirin as compared to aspirin alone after stroke or TIA: a systematic review. - Yan Huang; Man Li; Jian-Yong Li; Min Li; Yuan-Peng Xia; Ling Mao; Bo Hu (PLoS ONE)
Background and purpose Given the high risk of stroke after TIA (transient ischemia attack) or stroke and the adverse reaction of bleeding of antiplatelets, we undertook a meta-analysis, reviewed randomized controlled trials (RCTs) comparing aspirin plus clopidogrel with aspirin alone to determine the efficacy and adverse reaction of bleeding of the two protocols in the prevention of stroke. Methods We analyzed the incidences of stroke, bleeding and severe bleeding by using fixed-effect model or random-effect model on the basis of the result of heterogeneity test. Results Five qualified RCTs satisfied the inclusion criteria. We found that treatment with aspirin plus clopidogrel was associated with lower incidence of stroke (Risk Ratio (RR), 0.66, 95% confidence interval (CI), 0.47 to 0.93), higher incidence of bleeding (RR, 1.75, 95% CI, 1.48 to 2.05) as compared with aspirin-alone treatment. In terms of severe bleeding, no statistical difference existed between them (RR, 2.21, 95% CI, 0.25 to 19.52). Conclusion The combined use of aspirin and clopidogrel is more effective than aspirin alone for patients with previous TIA or stroke for the prevention of stroke, with risk of bleeding being higher. No statistical difference was found in severe bleeding between the two treatment protocols.